The English Students' Perspectives on Aaron O'Brien's Content on Vocabulary Usage - Amaliya Syamsar; Arya Eka Saputra; Astutie, Elma; Abdul Syahid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study examines the impact of Aaron O’Brien's educational content on social media in enhancing English vocabulary acquisition among EFL students. In the digital age, social media platforms have become valuable tools for language learning, offering students engaging and interactive ways to learn new vocabulary. The research used a quantitative survey method with a five-point Likert scale to assess students' perceptions of O’Brien's content. The survey, administered to 31 students, revealed that most participants found the content relevant and beneficial for learning vocabulary. The contextual approach used by O’Brien helped improve students' vocabulary retention. However, challenges in maintaining consistent engagement with the content were also noted, with factors like time management and distractions affecting students' motivation. Despite these challenges, the findings suggest that social media content, when integrated with formal educational settings, can enhance students' language learning experience. The study recommends exploring motivational strategies such as gamification or incentives to encourage regular interaction with educational content. Overall, the results indicate that educational content on social media, like that provided by O’Brien, has significant potential to support traditional language learning methods and improve vocabulary acquisition.